Staging joyful spectacles: Exploring the temporalities of positive affect in child-focused NGO programmes. (June 2021) - McCarthy, Annie
The child has long been a powerfully affective figure in development work – whether as an abject victim or a joyful symbol of brighter futures. While the power of children to produce emotions in donors has been well studied, far less attention has been given to children's own affective relationships with development organisations. This article explores the role of affect in children's participation in non-governmental organisation (NGO) programmes in Delhi, India. In particular, by focusing on spectacles of performance, this article highlights the importance of positive affects: happiness, fun, and joy in child-focused NGO programmes. Yet, rather than a cynical critique of the way children's joy is captured (typically in images) and translated into narratives of successful development, this article seeks to explore the possibilities for sincere ethnographic engagement with happiness itself. Drawing on the work of Sara Ahmed, and exploring the temporal dimensions of positive affects, I seek to engage seriously with children's joyful experiences in development programmes, while simultaneously questioning any simplistic equation of child happiness with developmental success.